Dynamic regulation of the transcriptome and proteome of the equine embryo during maternal recognition of pregnancy - Alba Rudolf Vegas; Giorgia Podico; Igor F. Canisso; Heinrich Bollwein; Thomas Fröhlich; Stefan Bauersachs; Carmen Almiñana (FASEB BioAdvances, 2022)
Abstract During initial maternal recognition of pregnancy (MRP), the equine embryo displays a series of unique events characterized by rapid blastocyst expansion, secretion of a diverse array of molecules, and transuterine migration to interact with the uterine surface. Up to date, the intricate transcriptome and proteome changes of the embryo underlying these events have not been critically studied in horses. Thus, the objective of this study was to perform an integrative transcriptomic (including mRNA, miRNAs, and other small non‐coding RNAs) and proteomic analysis of embryos collected from days 10 to 13 of gestation. The results revealed dynamic transcriptome profiles with a total of 1311 differentially expressed genes, including 18 microRNAs (miRNAs). Two main profiles for mRNAs and miRNAs were identified, one with higher expression in embryos ≤5 mm and the second with higher expression in embryos ≥7 mm. At the protein level, similar results were obtained, with 259 differentially abundant proteins between small and large embryos. Overall, the findings demonstrated fine‐tuned transcriptomic and proteomic regulations in the developing embryo associated with embryo growth. The identification of specific regulation of mRNAs, proteins, and miRNAs on days 12 and 13 of gestation suggested these molecules as pivotal for embryo development and as involved in MRP, and in establishment of pregnancy in general. In addition, the results revealed new insights into prostaglandin synthesis by the equine embryo, miRNAs and genes potentially involved in modulation of the maternal immune response, regulation of endometrial receptivity and of late implantation in the mare.